2018
DOI: 10.1155/2018/6196218
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Analysis of Government Subsidy and Performance Guarantee Policies in Relation to PPP Infrastructure Projects

Abstract: Sustainable operation of public-private partnership (PPP) infrastructure projects that are characterized by considerable external benefits is of vital importance. However, a liquidity shock might trigger an inefficient liquidation of a project by the special purpose vehicle (SPV) and the bank, whose objectives are to maximize the profits generated by the project. This study argues that performance guarantee and subsidy policies implemented by the government play a role in encouraging socially efficient decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, this method is often used to evaluate an isolated policy and not a series of policies on the same theme [47,49]. Policy documents are the main research materials in certain studies [24,27,28,38,39,[50][51][52]. Rothwell and Zegveld put forward a 3D (demand, environment and supply) analytical framework [53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this method is often used to evaluate an isolated policy and not a series of policies on the same theme [47,49]. Policy documents are the main research materials in certain studies [24,27,28,38,39,[50][51][52]. Rothwell and Zegveld put forward a 3D (demand, environment and supply) analytical framework [53].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ke et al [31] demonstrated through case studies that social capital regards "tax incentives" as an efficacious means of financing PPP projects. Shi and He et al [32] explored the influence of performance guarantee policies and government subsidies in preventing the inefficient dissolution of PPP infrastructure projects when external benefits are significant and assured. Despite these insights offering valuable recommendations for PPP policies, a comprehensive understanding of PPP policies remains elusive [33].…”
Section: Prior Research Into Ppp Project Policymentioning
confidence: 99%
“…Due to the characteristics of nonprofit, large quantities, and long construction time, the GICP requires stable policies to ensure its implementation and operation [72]. As for some projects in a public-private partnership, the government often provides land policy, tax incentives, and other supports to improve the investment benefits [73]. erefore, the stability and sustainability of policies have an essential impact on the growth of projects.…”
Section: Specific Analysis Of Risk Factors In Gicpmentioning
confidence: 99%